2016
DOI: 10.1016/j.fuel.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Fate of inorganic material during hydrothermal carbonisation of biomass: Influence of feedstock on combustion behaviour of hydrochar

Abstract: A series of high moisture content biomass have been processed by hydrothermal carbonisation (HTC) in a batch reactor at two temperatures (200 °C and 250 °C). The feedstocks processed include food waste, secondary sewage sludge, AD press cake, microalgae, macroalgae and a fibre derived from municipal derived wastes. In addition, three lignocellulosic biomass including miscanthus, willow and oak wood have been processed under identical conditions. The yields and properties of the resulting hydrochars includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
151
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(185 citation statements)
references
References 29 publications
16
151
0
4
Order By: Relevance
“…This indicates that a part of inorganic fraction of the original spent grain is lost. This is well in line with generally accepted consensus for hydrothermal carbonization and has been confirmed by a multitude of results from different studies, performed with different types of biomass [27,31,78,79]. Most certainly it is the case of HTC of BSG, even though a part of inorganic substance susceptible to precipitation into liquids is washed out from the malt, during the brewing process, which can be confirmed by a high content of macronutrients in various beers [80].…”
Section: Resultssupporting
confidence: 83%
“…This indicates that a part of inorganic fraction of the original spent grain is lost. This is well in line with generally accepted consensus for hydrothermal carbonization and has been confirmed by a multitude of results from different studies, performed with different types of biomass [27,31,78,79]. Most certainly it is the case of HTC of BSG, even though a part of inorganic substance susceptible to precipitation into liquids is washed out from the malt, during the brewing process, which can be confirmed by a high content of macronutrients in various beers [80].…”
Section: Resultssupporting
confidence: 83%
“…In the case of hydrothermal carbonization, unlike other thermal methods, mineral components are washed into the water and there is a noticeable decrease. The similar trend for inorganics removing from biomass in water during HTC is described in [8]. This is due to the destruction of lignocellulose, in which there is a large amount of mineral components.…”
Section: Element Analisys and Heating Valuessupporting
confidence: 70%
“…Escala et al [11] reported that conducting HTC and drying the hydrochar have energetic advantages compared with drying the sewage sludge for thermal disposal treatment. In addition, the HTC-pretreated sewage sludge is reported to have improved combustion properties compared to the pyrochar and raw sludge [6,9,12,13]. In terms of gasification of the biochar, Alvarez-Murillo et al [5] studied the steam gasification characteristics of the hydrochar derived from olive stone as a representative of lignocellulosic biomass.…”
Section: Introductionmentioning
confidence: 99%